IMPLEMENTASI PENJUALAN LANGSUNG BERJENJANG SYARIAH PADA FINANSIAL TEKNOLOGI PAYTREN (STUDI KASUS AGEN-AGEN PAYTREN DI KABUPATEN GRESIK) - Akhmad Firdaus Rostyanta; Muhammad Nafik Hadi Ryandono (Universitas Airlangga, 2019)
The purpose of this study was to determine how the application of sharia tiered system of direct sales on paytren and regulatory compliance PLBS in a fatwa on direct sales tiered sharia has been issued by the National Sharia Council in Indonesia. Paytren which is shaded by PT. Veritra Internasional Sentosa was established in 2013 and already has several partners spread throughout the archipelago, the object intended in this study is an active partner of Paytren, both from the upline and downline sides and former users of Paytren. This study uses a qualitative approach with a descriptive case study strategy. Data collection was obtained by conducting interviews with 5 resource persons consisting of the following 2 uplines, each with a downline of 1 partner who was inactive and 1 partner of Paytren without being known to the upline and downline. The results of this study indicate the application of the foot system, the distribution of commissions and the rewards used by Paytren. In this study it was found that the implementation of the PLBS Paytren system still contained some of the PLBS fatwas that had not been fulfilled and complied with by all Paytren partners.Keywords: Islamic Tiered Direct Selling, Paytren, Islamic Financial Management